2018
DOI: 10.1002/mawe.201700201
|View full text |Cite
|
Sign up to set email alerts
|

A study on annealing‐induced softening in cold drawn Cu−Cr−Sn alloy

Abstract: The softening behavior of a 60 % cold‐drawn Cu‐0.48Cr‐0.16Sn alloy during annealing at temperatures between 450 °C and 750 °C was investigated. The mechanical properties and microstructures evolution of the alloy in both as‐drawn and annealed conditions were analyzed using hardness measurement, transmission electron microscopy (TEM) and electron back‐scatter diffraction (EBSD) technique. The results showed that the softening behavior of the alloy was strongly affected by precipitate coarsening, recovery and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The activation energy of recrystallization of the 60% cold-drawn Cu0.54Cr0.17In alloy is Q R = 188.29 ± 18.44 kJ/mol, which is similar to the activation energy of the self-diffusion activation energy of Cu with 197 kJ/mol [24], and indicates that the recrystallization mechanism of the alloy is attributed mainly to Cu self-diffusion. The activation energy of the recrystallization of the Cu-Cr-In alloy is significantly higher than that of 70% cold-rolled pure Cu with 58 kJ/mol [25] and 60% cold-drawn Cu-Cr-Sn alloy with 117.958 kJ/mol [26], which indicates that elemental In addition can improve the activation energy of recrystallization of Cu-Cr alloys, and has a more obvious effect on delaying recrystallization than Sn addition. Mainly because of the big atomic radius of indium atoms, the atoms that are solutioned into the Cu lattice cause serious lattice distortion, which hinders dislocation movement and delays the recovery and recrystallization of the Cu-Cr-In alloy.…”
Section: Static Recrystallization Kineticsmentioning
confidence: 89%
See 1 more Smart Citation
“…The activation energy of recrystallization of the 60% cold-drawn Cu0.54Cr0.17In alloy is Q R = 188.29 ± 18.44 kJ/mol, which is similar to the activation energy of the self-diffusion activation energy of Cu with 197 kJ/mol [24], and indicates that the recrystallization mechanism of the alloy is attributed mainly to Cu self-diffusion. The activation energy of the recrystallization of the Cu-Cr-In alloy is significantly higher than that of 70% cold-rolled pure Cu with 58 kJ/mol [25] and 60% cold-drawn Cu-Cr-Sn alloy with 117.958 kJ/mol [26], which indicates that elemental In addition can improve the activation energy of recrystallization of Cu-Cr alloys, and has a more obvious effect on delaying recrystallization than Sn addition. Mainly because of the big atomic radius of indium atoms, the atoms that are solutioned into the Cu lattice cause serious lattice distortion, which hinders dislocation movement and delays the recovery and recrystallization of the Cu-Cr-In alloy.…”
Section: Static Recrystallization Kineticsmentioning
confidence: 89%
“…Crystals 2020, 10, x FOR PEER REVIEW 10 of 12 [26], which indicates that elemental In addition can improve the activation energy of recrystallization of Cu-Cr alloys, and has a more obvious effect on delaying recrystallization than Sn addition. Mainly because of the big atomic radius of indium atoms, the atoms that are solutioned into the Cu lattice cause serious lattice distortion, which hinders dislocation movement and delays the recovery and recrystallization of the Cu-Cr-In alloy.…”
Section: Static Recrystallization Kineticsmentioning
confidence: 99%
“…Li et al [ 20 ] found the tensile strength and electrical conductivity of the 80% cold-rolling Cu-0.67Cr-0.23Sn alloy were increased to 566.3 MPa and 73.3% IACS during aging at 400 °C for 120 min. Luo et al [ 21 ] obtained that the activation energy of recrystallization of the 60% cold-drawn Cu-0.48Cr-0.16Sn alloy is about 117.9 kJ/mol. In this work, the influence mechanism of Sn addition on microstructure and property evolution was further studied.…”
Section: Introductionmentioning
confidence: 99%
“…As a typical type of aging hardening alloys, Cu-Cr based alloys have high strength and moderate electrical conductivity, thus they are being applied to contact wires for high speed trains [1][2][3][4], lead frames [5][6][7], heat transfer [1,8], and so on. There are normally two ways to improve the alloy performance-optimization of heat treatment and addition of alloying elements [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%